Callable Contingent Capital: Valuation and Default Risk - Tian, Weidong (Management Science, 2018)
This paper proposes the use of contingent capital with a call provision, in which the insurer has an option to redeem the contingent capital at any time. I characterize in detail a unique dynamic equilibrium of common stock, subordinated contingent capital, and a senior standard bond under a simple yet sufficient and necessary condition that can be implemented easily. I further show that the issuance of callable contingent capital does not affect the default risk of an outstanding senior standard bond. As a result, callable contingent capital provides an alternative design for contingent capital using a prudential capital structure for a bank that is “too big to fail.” This paper was accepted by Jerome Detemple, finance.